2020
DOI: 10.3390/cancers12123800
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Fecal Microbiota with and without Invasive Cervical Cancer and Its Application in Early Diagnosis

Abstract: The fecal microbiota is being increasingly implicated in the diagnosis of various diseases. However, evidence on changes in the fecal microbiota in invasive cervical cancer (ICC) remains scarce. Here, we aimed to investigate the fecal microbiota of our cohorts, develop a diagnostic model for predicting early ICC, and identify potential fecal microbiota-derived biomarkers using amplicon sequencing data. We obtained fecal samples from 29 healthy women (HC) and 17 women with clinically confirmed early ICC (CAN). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Recent studies have suggested a potential role of Prevotella as an intestinal pathobiont related to oral cancer ( Karpiński, 2019 ), colorectal cancer ( Flemer et al., 2017 ; Peng et al., 2020 ), and lung cancer ( Tsay et al., 2018 ). In particular, this genus has been recognized as a prominent gynecologic and obstetric pathogen positively associated with cervical lesions, including bacterial vaginosis ( Marconi et al., 2012 ), cervical intraepithelial neoplasia ( Mitra and MacIntyre, 2020 ), cervical cancer ( Kang et al., 2020 ), and intrauterine infections ( Knoester et al., 2011 ). Herein, it is interesting to note that Prevotella has an important role in the metabolism of proteins and peptides because many of the members within this genus are actively proteolytic and possess characteristic dipeptidyl peptidase activity ( Flint and H., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested a potential role of Prevotella as an intestinal pathobiont related to oral cancer ( Karpiński, 2019 ), colorectal cancer ( Flemer et al., 2017 ; Peng et al., 2020 ), and lung cancer ( Tsay et al., 2018 ). In particular, this genus has been recognized as a prominent gynecologic and obstetric pathogen positively associated with cervical lesions, including bacterial vaginosis ( Marconi et al., 2012 ), cervical intraepithelial neoplasia ( Mitra and MacIntyre, 2020 ), cervical cancer ( Kang et al., 2020 ), and intrauterine infections ( Knoester et al., 2011 ). Herein, it is interesting to note that Prevotella has an important role in the metabolism of proteins and peptides because many of the members within this genus are actively proteolytic and possess characteristic dipeptidyl peptidase activity ( Flint and H., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Ren et al 37 reported the successful prediction efficiency of early hepatocellular carcinoma in their cross-regional study. Kang et al 38 investigated fecal microbiota of female cohort and discovered potential biomarkers to predict invasive cervical cancer in their Korea cohort. Furthermore, Loomba et al 39 identified 40 bacterial species associated with nonalcoholic fatty liver disease in a cohort from the United States.…”
Section: ■ Discussionmentioning
confidence: 99%
“…ML algorithms were recently widely applied to bioscience to find clues to solve living organisms’ complex interactions. , Prominent research on human subjects established microbiome applications to predict different clinical phenomena. , Ren et al reported the successful prediction efficiency of early hepatocellular carcinoma in their cross-regional study. Kang et al investigated fecal microbiota of female cohort and discovered potential biomarkers to predict invasive cervical cancer in their Korea cohort. Furthermore, Loomba et al identified 40 bacterial species associated with nonalcoholic fatty liver disease in a cohort from the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that Dialister, Porphyromonas and Prevotella were enriched, whereas Alistipes, Bacteroides and Lachnospiracea showed a relatively low abundance in cancer group compared with the control group [93]. In a recent study, a higher level of Prevotella was found in patients with cervical cancer than in healthy controls [94]. It was presumed that gut microbiota influenced cervical cancer development possibly through activation of inflammatory responses, but this assumption remained to be validated.…”
Section: Gut Microbiota and Urogenital System Tumormentioning
confidence: 99%